Multidisciplinary collaborative approach for management of adrenal tumors: Outcomes of minimally invasive adrenalectomy at a single center. Issue 3 (August 2021) - Mahajan, Rahul; Kotwal, Suman; Mahajan, Arti; Anjali,; Manhas, Amit
Introduction: Laparoscopy is currently the gold standard for the management of adrenal tumors as it is associated with less morbidity. Owing to technological advances, even large adrenal tumors are currently amenable to laparoscopic removal. In this work, we describe our multidisciplinary collaborative approach for management of adrenal tumors at a single center. Material and methods: Between January 2017 and January 2020, 18 patients with adrenal lesions were operated at our center. Five of these patients had incidentalomas. All patients were evaluated in coordination with endocrinologists and anesthetists. All patients underwent transperitoneal laparoscopic adrenalectomy. The surgical complications were classified as per Clavein-Dindo system. All patients with pheochromocytoma and Cushing syndrome were followed up by the endocrinologist for further evaluation and titration of glucocorticoids and antihypertensive medication. Results: Two out of the 18 patients had American Society of Anesthesiologists (ASA) physical status III. Out of the 18 patients, only one required conversion to open surgery. Five patients developed intraoperative hypertensive crisis while three patients developed hypotensive crisis. All patients were ambulated on the first postoperative day and were discharged on the third post operative day. None of the patients developed any major (Clavein-Dindo III–V) intra operative or post operative complications. Conclusion: Laparoscopic adrenalectomy is the procedure of choice for adrenal tumors. A multi-disciplinary approach involving the endocrinologist, anesthesiologist, and laparoscopic surgeon can help achieve favorable outcomes.